Lactate Dehydrogenase Levels In Leukemias - K.N PUJARI; S. P. JADKAR; G. J. BELWALKAR (International Journal of Pharma and Bio Sciences, 2012)
Lactate dehydrogenase, a pyridine-linked enzyme found virtually in all animal and human tissues, functions primarily in the metabolism of glucose, catalyzing the reduction of free pyruvate to lactate during the last step of glycolysis, as well as the conversion of lactate to pyruvate during gluconeogenesis. Its concentration is highest in liver followed in descending order in skeletal muscle, heart and kidney.We have determined the lactate dehydrogenase activity in the serum of leukemic patients and these levels were significantly high as compared to control. In respect to sex, the mean lactate dehydrogenase levels in females (1722.4 ± 1557.9) were found to be more than that in males (1393.5 ± 1197.6). However, we found a significant difference only in patients with chronic myeloid leukemia; whereas in respect to age, the mean lactate dehydrogenase levels were found to be elevated in 11- 20 years (1935.9 ± 1684.2) and lowered in age group greater than 51 years (1288.9 ± 1214.3). We observed highly significant (p<0.001) lactate dehydrogenase levels in all types of leukemias with respect to age.Our result suggests that increased cellular lactate dehydrogenase activity reflects a shift towards anaerobic metabolism and increased glycolysis in the cytoplasm of malignant cells accompanied by a high turnover rate. In evaluation of lactate dehydrogenase level in patients with leukemia could represent an additional and useful parameter in determining the clinical and prognostic aspect of the disease.